Ten years of anti-HPV vaccinations: what do we know? - Jach, Robert; Basta, Antoni; Kotarski, Jan; Markowska, Janina; Paszkowski, Tomasz; Dębski, Romuald; Rokita, Wojciech; Kędzia, Witold; Kiszka, Krystyna (Menopause Review/Przegląd Menopauzalny, 2016)
Human papillomavirus (HPV) is one of the most important carcinogens in humans. Vaccines against HPV are now considered the first anti-cancer vaccinations. Since 2007, in many developed countries, there have been recommendations present for preventive vaccines against HPV. At present, the degree of implementation of these recommendations depends on a number of country-specific factors such as the health care system organization or the ways of funding. HPV vaccines are primarily to prevent the development of cervical cancer and other genital cancers. Therefore, only their long-term effectiveness can be measured, when a correspondingly large cohort of vaccinated teenagers reaches the age of the greatest incidence of these cancers. However, great care should be taken in assessing the results of vaccinations due to the possibility of misinterpretation and possible erroneous data. Undoubtedly, teenagers are the target population of HPV vaccines. However, vaccinating young sexually active women is also justified from an individual point of view. A 9-valent vaccine has been registered in the USA and in Europe – including Poland – as one of the three preventive vaccines. It is recommended to vaccinate women between 13 and 26 and men between 13 and 21, previously unvaccinated. It is also recommended to vaccinate men aged 26 years or less who have sexual relations with other men and people with reduced immunity, including HIV-positive people who have not been vaccinated previously.